Acute pericarditis - Tonini,Márcio (2015)
Summary Acute pericarditis is a common disease caused by inflammation of the pericardium, usually benign and self-limited and can occur as an isolated or as a manifestation of a systemic disease entity. Represents 5% of all causes of chest pain in the emergency room. The main etiology are viral infections, although it can also be secondary to systemic diseases and infections. The main complication of acute pericarditis is pericardial effusion, triggering a cardiac tamponade. The first line of treatment is the use of anti-inflammatory and or acetylsalicylic acid. Most patients have a good initial response to an NSAID associated to colchicine and became asymptomatic within a few days. This review article seeks to contemplate the main clinical findings and armed investigation to optimize the diagnosis of this important disease, as well as addressing their therapeutic management.